Investigational nucleoside and nucleotide polymerase inhibitors and their use in treating hepatitis C virus. (September 2014) - Gentile, Ivan; Coppola, Nicola; Buonomo, Antonio Riccardo; Zappulo, Emanuela; Borgia, Guglielmo
<x xml:space="preserve">Abstract</x> Introduction: About 150 million people worldwide are estimated to be chronically infected with the hepatitis C virus (HCV). Successful antiviral treatment can stop the progression of the disease toward liver cirrhosis, hepatocellular carcinoma and death. IFN has been the drug of choice and the backbone of all combinations in the past two decades. However, an IFN-free combination (sofosbuvir and ribavirin) has been recently approved for genotypes 2 and 3 patients with many other drugs in preclinical and clinical development. Areas covered: This review focuses on investigational nucleoside or nucleotide inhibitors of viral polymerase that are potential treatments of HCV. The article reviews drugs that are currently under investigational status. Expert opinion: Currently, mericitabine has the most robust data but its efficacy appears to be less than optimal. Other drugs such as ALS-2200 (and its diastereomer VX-135) and BMS-986094 are promising but the data in humans are too scanty to draw conclusions about their future role at this current point in time. Other promising molecules are LG-7501, ACH-3422 and EP-NI266, although no clinical studies have been performed thus far, so this must be rectified. Another drug of promise GS-6620 has displayed a high degree of pharmacokinetic and pharmacodynamic variability, which makes further development unlikely.